A simulation and experimental study of electrochemical pH control at gold interdigitated electrode arrays. (1st November 2021) - O'Sullivan, Benjamin; Patella, Bernardo; Daly, Robert; Seymour, Ian; Robinson, Caoimhe; Lovera, Pierre; Rohan, James; Inguanta, Rosalinda; O'Riordan, Alan
Highlights: Electrochemical simulations confirm the viability of a pH control method at interdigitated microband arrays pH control simulations are validated using an interdigitated array of gold electrodes confirming the model. Electrochemical pH control was visualized by means of a pH dye, methyl red andapplied to the detecton of mercury in water. Abstract: In electroanalysis, solution pH is a critical parameter that often needs to be tailored and controlled for the detection of particular analytes. This is most commonly performed by the addition of chemicals, such as strong acids or bases. Electrochemical in-situ pH control offers the possibility for the local adjustment of pH at the point of detection, without the need for additional reagents. Finite element analysis (FEA) simulations have been performed on interdigitated electrodes, to guide experimental design in relation to both electroanalysis and in-situ control of solution pH. No previous model exists that describes the generation of protons at an interdigitated electrode arrays in solution with one comb acting as a protonator, and the other as the sensor. In this work, FEA models are developed to provide insight into the optimum conditions necessary for electrochemical pH control. The magnitude of applied galvanostatic current has a direct relation to the flux of protons generated and subsequent change in pH. Increasing the separation between the electrodes increases the time taken for protons to diffuse across the gap between the electrode combs. The final pH achieved after 1 second, at both protonator and sensor electrodes, was shown to be largely uninfluenced by a solution's initial pH. The impact of buffer concentration was also modelled and investigated. In practice, the pH at the electrode surface was probed by means of cyclic voltammetry, i.e., to identify the potential of the gold oxide reduction peak. A pH indicator, methyl red, was used to visualise the solution pH change at the electrodes, comparing well with the model's prediction. Finally, we show that in-situ pH controlled detection of mercury in water, using square wave stripping voltammetry, is almost identical to samples acidified to pH 3.5 using nitric acid.